Lost city of Shang - Eder, Stephen; Ward, Berley; Waite, George; Burns, Steve; Willes, Ray.; Discovery Channel (Firm). ([S.l.] Terra Nova Television, 1996)
"In 1889, a man using a decayed tortoise shell as a cure for his malaria noticed that the shell was covered in mysterious inscriptions. The writing referred to a civilization known as the Shang-a civilization, which had long been dismissed as legend. Since then, historians found more evidence of this ancient city, but the city itself has never been found"--Container.
Distributed in the Philippines by MagnaVision, Quezon City.
Associate producer, Beverley Ward ; editor, George Waite ; for Discovery Channel-executive producer, Tomi Bednar Landis ; production manager, Sarah Hume ; director of production, Steve Burns ; narrator, Ray Willes.
Keywords: Excavations (Archaeology) -- China; China -- Civilization -- Shang dynasty, 1766-1122 B.C.; China -- Antiquities